2011
DOI: 10.1016/j.envpol.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated naphthalenes (PCNs) in riverine and marine sediments of the Laizhou Bay area, North China

Abstract: a b s t r a c t PCN congeners were analyzed in marine and riverine sediments of the Laizhou Bay area, North China. Concentrations of PCNs ranged from 0.12 to 5.1 ng g À1 dry weight (dw) with a mean value of 1.1 ng g À1 dw.The levels of PCNs varied largely, with industrial group approximately ten folds higher than those of the rural in riverine sediment. A strong impact by direct discharge from local factories was suggested. Similar compositional profiles were found within groups. High resemblance of compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
3
34
1
1
Order By: Relevance
“…The southern coast (sites F1, F2, and F3 in Zone 1) of the Laizhou Bay is highly influenced by the adjacent land use pattern (Pan et al, 2011a). ∑PFAA concentration levels in the nearby shore sediments were lower than the observed concentrations in the estuaries due to the broader river bed and the dilution effect.…”
Section: The Dynamics Of Distribution In Laizhou Baymentioning
confidence: 90%
See 3 more Smart Citations
“…The southern coast (sites F1, F2, and F3 in Zone 1) of the Laizhou Bay is highly influenced by the adjacent land use pattern (Pan et al, 2011a). ∑PFAA concentration levels in the nearby shore sediments were lower than the observed concentrations in the estuaries due to the broader river bed and the dilution effect.…”
Section: The Dynamics Of Distribution In Laizhou Baymentioning
confidence: 90%
“…The general information of Laizhou Bay and its adjacent region was introduced by Pan et al (2011aPan et al ( , 2011b. Twenty-six surface (0-10 cm) coastal sediment samples and twenty-four river sediment samples were collected in September and October, 2009, in Laizhou Bay and its adjacent rivers using a stainless steel grab sampler.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been suggested that different PCN emission patterns may exist between fluidized bed and some grate MSW incinerators Weber et al 2001). The characteristics of PCN profiles from different cataloged sources have been applied to identify the specific source of PCNs in the environment (Schneider et al 1998;Helm and Bidleman 2003;Pan et al 2011). The major sources of PCNs in the environment were the technical formulations of PCNs (such as the Halowax series), industrial thermal processes, and impurities in technical formulations of PCBs (Abad et al 1999;Yamashita et al 2000;Ba et al 2010;Liu et al 2010).…”
Section: Profiles Of Emitted Pcnsmentioning
confidence: 99%